A METHOD OF CALCULATING WEAPON EFFECTIVENESS INDEX USING MUNITION TRAJECTORY AND VULNERABILITY DATA - Lee, Sunju; Rhie, Ye Lim; Lee, Sangjin; Oh, Hyun-Shik (International Journal of Industrial Engineering: Theory, Applications and Practice, 2023)
This paper proposes a novel method for calculating the weapon effectiveness index (WEI) by considering various engagement and environmental factors. The calculation is performed by determining the munition trajectory and using the target vulnerability data. Unlike the existing method that considers only the end state of a munition, the proposed method considers the effects of aiming errors, ballistic errors, and environmental conditions when calculating the munition trajectory. The vulnerability data represent the probability of kill (Pk) on the damage assessment (DA) plane corresponding to the impact angle. This paper describes the process of determining the impact point, identifying the appropriate DA plane, calculating the hit position on the DA plane, and obtaining the specific Pk. As a case study, a tank-to-armored vehicle engagement scenario is simulated. The proposed method is verified through a review of the simulation models and the simulation results by modeling and simulation system domain experts and weapon systems development domain experts.